FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN DI INDONESIA - Guruh Hari Ramadhan (2022)
This study aims to determine the effect of foreign ownership, public ownership, institutional ownership, firm size, profitability, and leverage on the disclosure of Corporate Social Responsibility (CSR). CSR is measured using the Standard GRI measurement index. Foreign ownership is measured by dividing the total foreign ownership shares by the total outstanding shares, public ownership is measured by dividing the total public ownership shares by the total outstanding shares, institutional ownership is measured by dividing the total institutional ownership shares by the total outstanding shares, company size is measured by the natural logarithm of total assets , profitability is measured using Return Of Assets (ROA), and leverage is measured using Debt to Assets Ratio (DAR). Data collection uses the documentation method, namely the collection of secondary data from existing sources such as annual reports and sustainability reports obtained from the IDX official website and the official website of each company. The analytical method used is multiple linear regression analysis using STATA version 14. The population used in this study are manufacturing and mining companies listed on the Indonesia Stock Exchange for the period 2018-2020. The research sample was determined using purposive sampling and obtained 18 companies that meet the criteria. The results show that partially foreign ownership, public ownership, firm size, profitability, and leverage have no effect on CSR disclosure, while institutional ownership has a significant negative effect on CSR disclosure.